Biofumigation with the endophytic fungus Nodulisporium spp. CMU-UPE34 to control postharvest decay of citrus fruit - Nakarin Suwannarach (2018)
Forty-six fungal endophytes were isolated from Lagerstroemia loudoni. Only one fungus, identified as Nodulisporium spp. CMU-UPE34, produced antifungal volatile compounds. It produced 31 volatile compounds, primarily composed of alcohols, acids, esters and monoterpene. The most abundant volatile compound was eucalyptol. In vitro tests showed that volatile compounds produced by Nodulisporium spp. CMU-UPE34 inhibited or killed 12 different plant pathogens. In vivo mycofumigation with jasmine rice grain cultures of Nodulisporium spp. CMU-UPE34 controlled green mold decay on Citrus limon caused by Penicillium digitatum, blue mold decay of Citrus aurantifolia and Citrus reticulata caused by P enicillium expansum. Nodulisporium spp. CMU-UPE34 has potential as a biofumigant for controlling postharvest disease. © 2012.